The Use of Love Language in Interpersonal Relationships - Wahyuni, Rani Sri (Dinamika: Jurnal Bahasa, Sastra, dan Pembelajarannya, 2025)
This study aims to analyze the role of love in interpersonal relationships between partners, friends, and in the work environment, between superiors and subordinates, which seeks to strengthening interpersonal relationships. The technique used in this study is a qualitative approach, with the field observation method and in-depth interviews with several couples/respondents as the sample. Data analysis in this study is to observe verbal and non-verbal interactions between twenty respondents/resource persons, including couples, superiors, subordinates, and friends, during the in-depth interview session. It can be seen that the results show that the use of informal, rich lexical language and non-verbal signals plays an important role in strengthening emotional bonds and increasing understanding between individuals. The results of the conversation data interview show that there are many differences between respondents and between one partner and another, depending on whether or not they have established a relationship. The findings show that the expression of love, both verbal and non-verbal, contributes significantly to satisfaction in their relationship. This study can also identify the five main love languages expressed by respondents, namely in the form of affirmation words, quality time, receiving gifts, service actions, and physical touch.